The role of electricity transmission infrastructure. - Gerbaulet, Clemens (Springer Nature, 2018)
The infrastructure required to assure a reliable, clean, and economic electricity system is among the crucial conditions that have to be established for the energiewende to succeed. This chapter summarizes issues surrounding electricity transmission in the context of the energiewende. Even though infrastructure is an important ingredient of the energiewende, its importance has been exaggerated in the policy debate and in the public debate as well. Often hailed as a critical factor in the energiewende and sometimes as the final nail in its coffin transmission infrastructure has not been a demonstrable obstacle to the energiewende thus far, thanks to the highly developed network inherited from the old system and its continuous improvement over the last decade. Even in the medium term - that is, into the 2020s no serious roadblocks for the energiewende are to be expected, provided that the transmission system operators (TSOs) and regulatory agencies stick to the path of transmission expansion that has proven reliable so far. Sections 8.2 and 8.3 describe network planning and development from its inception in the 2000s until today. Over this period, a new method of transmission planning has been implemented, creating more transparency for transmission policies, which had not been open to public scrutiny under the old system. Section 8.4 then traces a decade of network development in Germany. As elaborated in detail, rates of transmission investment remain consistent over the years, and important connections, such as links between the former GDR and West Germany have been completed. Section 8.5 discusses the current debate of introducing multiple price zones in Germany. Moreover, it summarizes results of a study on the effects of establishing multiple price zones in Germany suggesting that there is no need to split the German electricity market into zones. Section 8.6 details an interesting recent development: the explicit integration of carbon dioxide (CO2) constraints into network planning. Finally, Sect. 8.7 concludes.
Keywords: Energie; Energiewende; Technische Infrastruktur; Energieleitung; Versorgungsleitung; Stromnetz; Netzausbau; Trassenführung